2015
DOI: 10.1002/star.201500022
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of a novel β-cyclodextrin modified cationic polyacrylamide and its application for enhancing oil recovery

Abstract: The methyl acrylamide propyl dimethyl butyl ammonium chloride (DMAPMA-C) and allyl-b-cyclodextrin (A-b-CD) were synthesized separately and then jointly copolymerized with acrylamide (AM) to form a novel cationic acrylamide polymer P(AM/A-b-CD/DMAPMA-C) through aqueous redox free-radical polymerization. The structure of the copolymer was characterized using Fourier transform infrared spectroscopy (FT-IR), nuclear magnetic resonance (NMR) and scanning electron microscopy (SEM). Subsequently, a series of experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
10
0
2
Order By: Relevance
“…Por outro lado, os agentes reticulantes de natureza orgânica envolvem a ocorrência de ligações covalentes com os grupos funcionais do polímero, unindo duas ou mais cadeias poliméricas. Sendo mais estáveis termicamente, foram reportadas aplicações desses sistemas em temperaturas de até 156 °C (JIA et al, 2012;LENJI et al, 2018;JIA et al, 2017). Este comportamento pode ser atribuído à formação de ligações mais resistentes entre os polímeros e os agentes reticulantes (AL-MUNTASHERI et al, 2007;JIA et al, 2012;SENGUPTA et al, 2014;MA et al, 2017;CHEN, 2018).…”
Section: Hidrogéis Para Controle De Conformidade Em Reservatórios De unclassified
See 1 more Smart Citation
“…Por outro lado, os agentes reticulantes de natureza orgânica envolvem a ocorrência de ligações covalentes com os grupos funcionais do polímero, unindo duas ou mais cadeias poliméricas. Sendo mais estáveis termicamente, foram reportadas aplicações desses sistemas em temperaturas de até 156 °C (JIA et al, 2012;LENJI et al, 2018;JIA et al, 2017). Este comportamento pode ser atribuído à formação de ligações mais resistentes entre os polímeros e os agentes reticulantes (AL-MUNTASHERI et al, 2007;JIA et al, 2012;SENGUPTA et al, 2014;MA et al, 2017;CHEN, 2018).…”
Section: Hidrogéis Para Controle De Conformidade Em Reservatórios De unclassified
“…A combinação polímero-carga exibe novas propriedades por conta de fortes interações entre as moléculas poliméricas e a sílica, as quais são atribuídas à formação de ligações hidrogênio entre o grupo carbonila, ou outros grupos polares, e o silanol (SiOH) presente na superfície da nano-partícula (LAI et al, 2016;MA et al, 2017;CHEN et al, 2018;HU et al, 2015); LASHARI et al, 2018).…”
Section: Autores Agente De Reforçounclassified
“…β-Cyclodextrins (β-CDs) are abundant in nature and have biodegradable and environmentally friendly properties, can be modified by chemical method [10,11], while at the same time, their hydrophobic cavity has a certain inclusion property for organic molecules with moderate radius, and can form inclusion compounds with aromatic compounds through host-guest recognition, so they have high removal efficiency for aromatic compounds in aromatic dye wastewater. It was reported that [12][13][14][15][16][17], β-CDs combined with traditional flocculating materials such as polyacrylamide can prepare new flocculating materials with high selectivity and high absorption efficiency for organic pollutants. However, in these related references, harmful organic reagents such as polyacrylamide are used in large quantities, which cannot be considered environmentally friendly.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Recently, hydrophobic associating polymers have been widely used in oileld applications, such as acidizing treatments, 7,8 drilling and completion uids, and polymer ooding. [9][10][11][12] In oileld applications, the hydrophobic associating polymer is adsorbed on the reservoir for the interaction of the polymer and the reservoir, which may have some effect on the reservoir. The adsorption behavior of hydrophobic associating polymers has attracted signicant attention from many researchers.…”
Section: Introductionmentioning
confidence: 99%